Adaptive psychological functioning and burnout in teachers: Implications on instructional processes - Romero, Valeria; Núñez, José Carlos; Freire, Carlos; Ferradás, María del Mar (Psychology, Society & Education, 2023)
Given the high levels of burnout in the teaching profession, there is a growing interest in identifying the personal resources that would favor the positive psychological functioning in this group. From this emerging perspective, the present study had two objectives: (1) analyze the effect of psychological capital and job satisfaction on burnout in teachers; (2) determine how this syndrome affects the instructional practice (self-efficacy for teaching self-regulation strategies and teaching approach adopted). A structural equations model analysis was carried out with 113 teachers (90.3% women; Mage = 38.13; SD = 11.01) from pre-school, elementary school, compulsory secondary education and Bachillerato [optional higher secondary education]), selected through a convenience sample. Psychological capital and job satisfaction were shown to be negative predictors of burnout. In turn, this syndrome showed a direct negative effect on self-efficacy, and an indirect one on the student-centered teaching approach. These findings suggest that psychological capital and job satisfaction can be valuable resources to reduce teacher burnout and favor their adaptive job performance.